THE USE OF EMPLOYER BRANDING DIMENSIONS TO ATTRACT FRESH GRADUATES - Sekar Wulan Prasetyaningtyas; Michelle Sim; Brian Hariman Triantoro; Allen Allen (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2022)
One of the obstacles in the company recruitment process is the change of labor force generation. Indonesia has already shifted the labor force to generation Z. This research aims to examine the influence of employer branding dimensions consisting of work environment, compensation and benefits, corporate reputation, corporate vision and leadership, and corporate social responsibility in attracting work interests. This cross-sectional study with an online questionnaire to 306 fresh graduate respondents domiciled in Jakarta, Bogor, Depok, Tangerang, South Tangerang, and Bekasi (Jabodetabek). Data analysis uses linear regression methods. The study results indicate that all employer branding variables positively affect the intention to apply for a job. This aspect needs to be considered by the company in increasing the intention to apply for a job from fresh graduate employees’ candidates who are currently generation Z. The work environment has the highest average value towards applying for a job. It can be due to the primary purpose of generation Z is choosing the company where they will work in the comfort of the workplace atmosphere.